Factors influencing left atrial volume in a population with preserved ejection fraction: Left ventricular diastolic dysfunction or clinical factors?. Issue 4 (October 2016) - Lee, Seitetsu L.; Daimon, Masao; Nakao, Tomoko; Singer, Daniel E.; Shinozaki, Tomohiro; Kawata, Takayuki; Kimura, Koichi; Hirokawa, Megumi; Kato, Tomoko S.; Mizuno, Yoshiko; Watanabe, Masafumi; Yatomi, Yutaka; et al.
Abstract: Background: Increased left atrial volume (LAV) predicts a higher incidence of cardiovascular events and is widely recognized as a major surrogate marker of left ventricular (LV) diastolic dysfunction (DD). Although the pathophysiology of LA enlargement is probably multifactorial, few studies have examined comprehensively the clinical factors that lead to LA enlargement in the absence of valvular disease or LV systolic dysfunction. Therefore, we investigated associations between LAV and several clinical and echocardiographic parameters including DD. Methods: We enrolled 557 subjects without significant valve disease or LV systolic dysfunction from the health check-up clinic retrospectively. We performed univariable and multivariable linear regression using ln LAV index as the dependent variable and the following independent variables: gender, age, smoking status, drinking habit, hypertension, diabetes, body mass index (BMI), LV ejection fraction, DD, LV mass index, hemoglobin, serum creatinine, serum total cholesterol, serum uric acid, serum sodium, and serum iron. Results: In multivariable analysis, LAV index was independently associated with BMI, lower hemoglobin, and moderate and severe DD compared with normal diastolic function ( p < 0.001), but not with mild DD ( p = 0.70). Conclusions: LA enlargement was independently associated with moderate and severe DD, but not with mild DD. Furthermore, obesity and lower hemoglobin were associated with LAV independently of DD.